CERCETĂRI HELMINTOLOGICE CU IMPACT INVAZIV STABILITE LA CULTURA DE MAZĂRE (PISUM SATIVUM L.) ÎN CONDIȚIILE DE MEDIU ALE REPUBLICII MOLDOVA - Iurcu-Străistaru, Elena; Toderaş, Ion; Bivol, Alexei; Rusu, Ştefan; Sasanelli, Nicola; Rusu, Viorelia; Gliga, Olesea; Gologan, Ion (CEP USM, 2024)
One important factor in increasing the productivity and quality of peas (Pisum sativum L.) grown in the conditions of the Republic of Moldova is the phytosanitary control of parasitic helminthological fauna. The investigations were carried out in four administrative districts of the central areas, covering twelve pea sectors from various regions specialized in the cultivation of fabaceous plants. As a result of the helminthological protection investigations in peas, the parasitic degree was established for the first time, with comparative indices of number density ranging from 15 to 250 individuals per 100g of soil, and an abundance of 7–25% in spring. The frequency indices of the attack degree and extensiveness of helminthological affections showed more advanced values (5–30%) in the summer, varying across plantation areas. The structure of the nematode parasite complexes was determined, consisting of eight genera, including six families and one order, classified according to their trophic specialization. There was a predominance of endoparasite and semiendoparasite species from the Heteroderidae, Tylenchidae, and Hoplolaimidae families.
HELMINTOLOGICAL RESEARCH WITH ESTABLISHED INVASIVE IMPACT ON THE PEA CROPS (PISUM SATIVUM L.) IN THE ENVIRONMENTAL CONDITIONS OF THE REPUBLIC OF MOLDOVA
Keywords: pea plantations; nematodes community; fitosanitary monitoring; diversity of species; abundance